Opferschutz und Erziehungsgedanke im Jugendstrafverfahren - Zapf, Jana Christina (Universitätsverlag Göttingen, 2012)
The dissertation investigates in which way the juvenile penal law allows for victim rights. This ques-tion is treated dogmatically and discussed in the lights of an empirical survey made specifically for this dissertation.